AAML0523: A report from the Children's Oncology Group on the efficacy of clofarabine in combination with cytarabine in pediatric patients with recurrent acute myeloid leukemia. Issue 16 (25th April 2014) - Cooper, Todd M.; Alonzo, Todd A.; Gerbing, Robert B.; Perentesis, John P.; Whitlock, James A.; Taub, Jeffrey W.; Horton, Terzah M.; Gamis, Alan S.; Meshinchi, Soheil; Loken, Michael R.; Razzouk, Bassem I.
<x xml:space="preserve">Abstract</x> BACKGROUND The discovery of new, effective non–anthracycline‐based reinduction regimens for children with recurrent acute myeloid leukemia (AML) is critical. In this phase 1/2 study, the tolerability and overall response rate of clofarabine in combination with cytarabine was investigated in children with recurrent/refractory AML. METHODS AAML0523 enrolled 49 children with AML in first recurrence or who were refractory to induction therapy. The study consisted of a dose‐finding phase (9 patients) and an efficacy phase (40 patients). Two children received clofarabine at a dose of 40 mg/m2/day and 47 children at a dose of 52 mg/m2/day. RESULTS Toxicities typical for intensive chemotherapy regimens were observed at all doses of clofarabine. The recommended pediatric phase 2 dose of clofarabine in combination with cytarabine was 52 mg/m2/day for 5 days. Of 48 evaluable patients, the overall response rate (complete remission plus complete remission with partial platelet recovery) was 48%. Four patients met conventional criteria for complete remission with incomplete count recovery. Twenty‐one of 23 responders subsequently underwent hematopoietic stem cell transplantation. The overall survival rate at 3 years was 46% for responders compared with 16% for nonresponders (P < .001). Patients found to have no minimal residual disease at the end of the first cycle by flow cytometric analysis had superior overall survival after 1 year (100% vs 38%; P = .01). CONCLUSIONS The combination of clofarabine and cytarabine yielded an acceptable response rate without excess toxicity in children with recurrent AML. The nearly 50% survival rate reported in responders is highly encouraging in these high‐risk patients and suggests that this combination is an effective bridge to hematopoietic stem cell transplantation. Cancer 2014;120:2482–2489. © 2014 American Cancer Society.